Method for measuring thickness of p-type layer of mercury cadmium telluride p-on-n structural material and application

The carrier concentration and mobility are measured by mercury saturation annealing and layer-by-layer chemical corrosion, and the p-type layer thickness of mercury cadmium tellurium p-on-n structural material is determined, which solves the problem of inaccurate measurement in the prior art and achieves high Accurate thickness measurement supports the research and development and mass production of high-performance infrared detectors.

CN119252747AActive Publication Date: 2025-01-03KUNMING INST OF PHYSICS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411263134.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-01-03
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The prior art cannot accurately measure the p-type layer thickness of mercury cadmium tellurium p-on-n structural materials, resulting in errors in process parameter design, affecting the performance and mass production of infrared detectors.

Method used

Through mercury saturation annealing treatment, electrical parameter measurement and layer-by-layer chemical corrosion, combined with the change curves of carrier concentration and mobility, the inflection point position of the p-type layer thickness is determined, and the p-type layer thickness is accurately measured.

Benefits of technology

It realizes high-precision measurement, supports the research and development and batch preparation of high-performance long-wave and very long-wave infrared detectors, ensuring the accuracy of material quality and process parameters.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252747A_ABST
    Figure CN119252747A_ABST
Patent Text Reader

Abstract

The invention discloses a method for measuring the thickness of a p-type layer of a mercury-cadmium-telluride p-on-n structural material and application, and the method comprises the steps: determining a changing curve of the carrier concentration and the mobility along with the thickness through measuring the carrier concentration and the mobility of the mercury-cadmium-telluride p-on-n structural material under different thicknesses; and accurately determining the thickness of the p-type layer on the basis of inflection points where the carrier concentration and the mobility tend to be stable on the change curve. The method is simple in operation and high in accuracy, can provide reference for back-end device process parameter design, and supports batch production of high-performance p-on-n structure infrared detectors. The method can provide reference for adjustment of preparation process parameters of the mercury cadmium telluride p-on-n structure material, and provides guarantee for optimization of material quality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to mercury cadmium telluride materials and device technologies, and in particular to a method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material and its application, which can provide an accurate p-type layer thickness value for a high-performance infrared detector preparation process. Background Art

[0002] Mercury cadmium telluride has become the most important material for the preparation of high-performance infrared detectors due to its advantages such as high quantum efficiency, low dark current, and the ability to achieve full infrared band detection by adjusting the components. According to the type of absorption layer, mercury cadmium telluride infrared detectors can be divided into two types: n-on-p and p-on-n, with the absorption layers being p-type and n-type mercury cadmium telluride materials, respectively. At the same doping concentration, the minority carrier lifetime of p-type materials is longer than that of n-type materials, so in theory the performance of n-on-p can be better than that of p-on-n. However, it is difficult to achieve low-concentration doping of p-type materials, and currently it is difficult to achieve the level of p-on-n structure devices in which the absorption layer is more easily doped with low concentrations. Mercury cadmium telluride p-on-n has also become the main technical route for the mass production of high-performance long-wave and very long-wave infrared detectors in the future.

[0003] For the preparation of HgCdTe p-on-n devices, it is extremely important to accurately obtain the thickness of the p-type layer, which will directly affect the control level of the device process, especially the electrode hole etching process. If the measured value of the p-type layer thickness is larger than the actual value, using a larger electrode hole depth when designing the process parameters may cause the p-type layer to be etched through and the pn junction to fail; if the measured value of the p-type layer thickness is smaller than the actual value, using a smaller electrode hole depth when designing the process parameters may cause the electrode hole to be too shallow, affecting carrier migration and reducing quantum efficiency. At present, the method of measuring the cross-sectional element distribution is often used to determine the thickness of the p-type layer. Since the element doping amount is generally very low, this method has high requirements for the accuracy of the test instrument. If the accuracy is insufficient, it is easy to cause large errors in the results; at the same time, this method cannot obtain the electrical thickness of the p-type layer, so the test itself is inaccurate.

[0004] At present, the method of measuring the cross-sectional element distribution is often used to determine the thickness of the p-type layer of HgCdTe p-on-n structure materials. However, this method is not accurate enough for two main reasons:

[0005] (1) The doping amount of the element is generally very low. This method requires a high accuracy of the test instrument. If the accuracy is insufficient, it is easy to cause large errors in the results.

[0006] (2) At the same time, this method cannot obtain the electrical thickness of the p-type layer, so the test result itself is inaccurate. Summary of the invention

[0007] The present invention aims to solve the above technical problems and provides a method for measuring the thickness of the p-type layer of HgCdTe p-on-n structural materials. The basic concept of the method includes: based on the accurate measurement of thickness, carrier concentration and mobility during the corrosion process, the thickness of the p-type layer can be determined electrically through the inflection point of the carrier concentration and mobility changing with thickness. The method is simple to operate and has high measurement accuracy, and can effectively support the research and development and mass production of high-performance long-wave, very long-wave and high-operating-temperature HgCdTe infrared detectors.

[0008] The technical solution of the present invention is:

[0009] A method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material comprises the following steps:

[0010] (1) Mercury saturation annealing: The prepared p-on-n structure HgCdTe material is subjected to mercury saturation annealing to eliminate mercury vacancies; at the same time, an n-type companion wafer is selected and subjected to mercury saturation annealing under the same conditions. The companion wafer and the n-type material in the p-on-n structure HgCdTe material are grown under the same conditions and have similar cutoff wavelengths;

[0011] (2) Thickness measurement: Measure the original thickness of the p-on-n structure HgCdTe material and the n-type companion film, denoted as h0 and h2, respectively. a ;

[0012] (3) Electrical parameter measurement: Clean the material surface and remove the oxide layer, measure the carrier concentration and mobility of the p-on-n structure HgCdTe material and the n-type companion plate, which are recorded as N0, μ0, and N a , μ a ;

[0013] (4) Chemical etching: chemical etching liquid is used to etch the p-on-n structure HgCdTe material. The thickness is h, and the h value can be adjusted according to the specific accuracy requirements, preferably in the range of 0.2 to 0.5 μm.

[0014] (5) Electrical parameter measurement again: measure the thickness of the remaining material, recorded as h1, and test the carrier concentration and mobility of the remaining material again, recorded as N1 and μ1 respectively;

[0015] (6) Chemical etching again and electrical parameter measurement: Repeat steps (4) and (5) to obtain multiple remaining thicknesses h2, h3, ..., h of the p-on-n structure HgCdTe material after multiple etchings. i , and multiple carrier concentrations N2, N3, ..., N i , multiple mobilities μ2, μ3, …, μ i , where i ≥ 2, indicating the number of corrosion times;

[0016] (7) Draw the relationship curve: Draw N i and μ i The curve of the change with the corrosion number i, N is determined on the curve i and μ i Both tend to a stable inflection point. At the same time, the carrier concentration and mobility at the inflection point are the same as the carrier concentration of the n-type companion plate (N a ) and mobility (μ a ) is similar, and the corrosion times of the inflection point are recorded as ip;

[0017] (8) Determine the thickness of the p-type layer: The thickness of the p-type layer is the difference between the original material thickness and the inflection point thickness, which is h p =h0-h ip .

[0018] According to a method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structural material provided by the present invention, the mercury cadmium telluride p-on-n structural material may be a double-layer material grown by liquid phase epitaxy (LPE), molecular beam epitaxy (MBE), chemical vapor deposition (CVD) and the like, or may be a material formed by performing p-type ion implantation on an N-type material.

[0019] According to a method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structural material provided by the present invention, the chemical etching solution adopts an organic or inorganic solution containing a bromine element, and the corrosion rate is adjusted by controlling the concentration. The corrosion rate is v, and the v value can be designed after comprehensive consideration of the accuracy requirements and the removal thickness h, and is preferably between 0.05μm / min and 0.5μm / min.

[0020] The present invention provides a method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structural material. The method can realize accurate measurement of the thickness of the p-type layer of the mercury cadmium telluride p-on-n structural material, provide a basis for adjusting the preparation process of the p-type layer, and realize accurate design of process parameters; at the same time, it can provide a reference for subsequent processes such as mesa etching and electrode hole etching, and effectively design a suitable etching depth.

[0021] Beneficial effects of the present invention:

[0022] The present invention measures the carrier concentration and mobility of the mercury cadmium telluride p-on-n structure material layer by layer, determines the change of carrier concentration and mobility with thickness, and accurately determines the thickness of the p-type layer based on the inflection point on the change curve. The method is simple to operate and has high accuracy. It can provide a reference for the design of device process parameters at the back end and support the mass production of high-performance p-on-n structure infrared detectors. The method can also provide a reference for the adjustment of the process parameters for the preparation of mercury cadmium telluride p-on-n structure materials and provide a guarantee for the optimization of material quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Surface optical morphology of the mercury cadmium telluride p-on-n structure material selected for use in an embodiment of the present invention.

[0024] Figure 2 The curve of carrier concentration and mobility versus thickness of HgCdTe p-on-n structure material and the determined value of the p-type layer thickness drawn for the embodiment of the present invention.

[0025] Figure 3 The response signal distribution diagram and blind pixel distribution diagram of the long-wave detector developed based on the p-type layer thickness provided in the embodiment of the present invention are shown. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below through examples in conjunction with the accompanying drawings. The given examples and drawings are only for illustrating the present invention, rather than for limiting the scope of the present invention.

[0027] The present invention provides the following specific embodiments.

[0028] A method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material comprises the following steps:

[0029] (1) Mercury saturation annealing: Prepare p-on-n structure HgCdTe materials and n-type companion wafers. The n-type companion wafers and the n-type materials in the p-on-n structure HgCdTe materials are both grown by horizontal tellurium-rich liquid phase epitaxy, with room temperature cutoff wavelengths of 6.35μm and 6.37μm, respectively. The p-type materials in the p-on-n structure HgCdTe materials are prepared by vertical mercury-rich liquid phase epitaxy technology containing in-situ As doping. The p-on-n structure HgCdTe materials and the n-type companion wafers are subjected to mercury saturation annealing under the same conditions to eliminate mercury vacancies.

[0030] (2) Thickness measurement: The original thickness of the p-on-n structure HgCdTe material and the n-type companion film were measured using an infrared spectrometer, which were h0 = 14.4 μm and ha = 12.5 μm, respectively.

[0031] (3) Electrical parameter measurement: After cleaning the material surface and removing the oxide layer, the carrier concentration and mobility of the p-on-n structure HgCdTe material and the n-type companion plate were measured using a Hall tester. The results were N0 = 2.28E15 cm -3 (N type), μ0=1.67E4cm 2 / Vs, and Na=3.16E14 cm -3 、μa=9.28E4 cm 2 / Vs;

[0032] (4) Chemical corrosion: Use chemical corrosion liquid to corrode the p-on-n structure mercury cadmium telluride material, adjust the corrosion rate to about 0.3μm / min, and the corrosion time is 1min.

[0033] (5) Electrical parameter measurement again: The thickness of the remaining material was measured, and h1 = 14.2 μm was obtained. The carrier concentration and mobility of the remaining material were tested again, and N1 = 2.06E15 cm -3 (N type), μ1=2.58E4 cm 2 / Vs;

[0034] (6) Re-chemical etching and electrical parameter measurement: Steps (4) and (5) are continuously repeated to obtain a plurality of remaining thicknesses h2, h3, ..., hi of the p-on-n structure HgCdTe material after multiple etchings, as well as a plurality of carrier concentrations N2, N3, ..., Ni, and a plurality of mobilities μ2, μ3, ..., μi, where i ≥ 2, indicating the number of etchings;

[0035] (7) Draw a relationship curve: Draw a curve of Ni and μi changing with the number of corrosion times i. The results are as follows Figure 2 As shown in the results, it can be found that there is an inflection point on the curve where both Ni and μi tend to be stable. At the same time, the carrier concentration and mobility at the inflection point are similar to the carrier concentration (Na) and mobility (μa) of the n-type companion plate. The etching times of the inflection point are recorded as ip = 8. The remaining thickness of the p-on-n structure HgCdTe material measured at this etching time is hip = 12.0μm.

[0036] (8) Determine the thickness of the p-type layer: The thickness of the p-type layer is the difference between the original material thickness and the inflection point thickness, that is, hp = h0 - hip = 14.4 - 12.0 = 2.4 μm.

[0037] like Figure 3 The figure shows the response signal distribution diagram and blind pixel distribution diagram of the long-wave infrared detector made of the material prepared by the same growth process as the p-on-n structure HgCdTe material selected in the embodiment, wherein the thickness of the p-type layer is hp=2.4 obtained by referring to the embodiment of the present invention. The detector has a scale of 640×512 (25μm center distance), a response signal non-uniformity of 5.4%, a blind pixel rate of 0.52%, and a good overall performance.

Claims

1. A method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material, characterized in that: The following steps are involved: (1) preparing a p-on-n structure HgCdTe material and an n-type companion wafer, performing a mercury saturation annealing treatment on the p-on-n structure HgCdTe material and the n-type companion wafer under the same conditions to eliminate mercury vacancies, wherein the companion wafer and the n-type material in the p-on-n structure HgCdTe material are grown under the same conditions, and their cutoff wavelengths are similar; (2) Measure the original thickness of the p-on-n structure HgCdTe material and the n-type companion piece, denoted as h0 and h a ; (3) Clean the material surface and remove the oxide layer, measure the carrier concentration and mobility of the p-on-n structure HgCdTe material and the n-type companion piece, and record them as N0, μ0 and N a , μ a ; (4) using chemical etching solution to corrode the p-on-n structure HgCdTe material to remove a thickness of h; (5) Measure the thickness of the remaining material, recorded as h1, and test the carrier concentration and mobility of the remaining material again, recorded as N1 and μ1 respectively; (6) Repeating steps (4) and (5) to obtain multiple residual thicknesses h2, h3, ..., h of the p-on-n structure HgCdTe material after multiple etchings i , and multiple carrier concentrations N2, N3, ..., N i and multiple mobilities μ2, μ3, …, μ i , where represents the number of corrosion, i≥2; (7) Draw N i and μ i The curve of the change with the corrosion number i, N is determined on the curve i and μ i Both tend to a stable inflection point. At the same time, the carrier concentration and mobility at the inflection point are the same as the carrier concentration N of the n-type companion piece. a and mobility μ a Similar, record the number of corrosion times of the inflection point as ip; (8) Determine the thickness of the p-type layer, the thickness of the p-type layer h p is the original material thickness h0 and the inflection point thickness h ip The difference h p =h0-h ip .

2. The method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material according to claim 1, characterized in that: The h value is designed according to specific accuracy requirements.

3. The method for measuring the thickness of the p-type layer of a mercury cadmium telluride p-on-n structure material according to claim 2, characterized in that: The h value is 0.2 to 0.5 μm.

4. The method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material according to claim 1, characterized in that: The mercury cadmium telluride p-on-n structure material is a double-layer material grown by liquid phase epitaxy LPE, molecular beam epitaxy MBE, or chemical vapor deposition CVD, or is a material formed by performing p-type ion implantation on an N-type material.

5. A method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material according to any one of claims 1 to 4, characterized in that: The chemical etching solution is an organic or inorganic solution containing bromine.

6. The method for measuring the thickness of the p-type layer of a mercury cadmium telluride p-on-n structure material according to claim 5, characterized in that: The corrosion rate v is adjusted by controlling the concentration of the chemical etching solution.

7. The method for measuring the thickness of the p-type layer of a mercury cadmium telluride p-on-n structure material according to claim 6, characterized in that: The corrosion rate v is designed after comprehensive consideration of the accuracy requirements and the removal thickness design.

8. The method for measuring the thickness of the p-type layer of a mercury cadmium telluride p-on-n structure material according to claim 7, characterized in that: The corrosion rate v is 0.05 μm / min to 0.5 μm / min.

9. Application of the method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structural material according to any one of claims 1 to 8, characterized in that: The thickness of the p-type layer of the mercury cadmium telluride p-on-n structure material measured by the method is used as a basis for adjusting the preparation process of the p-type layer, so as to realize the accurate design of the process parameters.

10. Application of the method for measuring the thickness of a p-type layer of a mercury cadmium telluride p-on-n structure material according to any one of claims 1 to 8, characterized in that: The thickness of the p-type layer of the mercury cadmium telluride p-on-n structural material measured by the method is used to design the etching depth of subsequent mesa etching and electrode hole etching.

Citation Information

Patent Citations

  • Method for measuring mercury cadmium telluride material pn junction depth

    CN101383306A

  • A method for testing the thickness of a metallic transition layer

    CN102269565A

  • Method of testing HgCdTe pn junction material

    CN109116270A

  • Method and device for measuring depth of ultra-shallow junction of double-sided solar cell

    CN110011617A

  • Method for detecting effective junction depth of PN junction of mercury cadmium telluride chip

    CN114141645A